Cortical Activation and Functional Connectivity Response to Different Interactive Modes of Virtual Reality (VR)-Induced Analgesia: A Prospective Functional Near-Infrared Spectroscopy (fNIRS) Study - Deng X; Jiang N; Huang Z; Wang Q (Journal of Pain Research, 2025)
Xue Deng,1,2 Naifu Jiang,3 Zhaoying Huang,4 Qi Wang5 1Department of Rehabilitation Medicine, The 8th Affiliated Hospital of Sun Yat-Sen University, Shenzhen, Guangdong Province, People’s Republic of China; 2Division of Occupational Therapy, Decker College of Nursing and Health Sciences, Binghamton University, Johnson City, NY, 13902, USA; 3CAS Key Laboratory of Human-Machine intelligence-Synergy Systems, Shenzhen Institutes of Advanced Technology (SIAT), Chinese Academy of Sciences (CAS), Shenzhen, Guangdong Province, People’s Republic of China; 4Department of Rehabilitation, Children’s Hospital of Chongqing Medical University, Chongqing Municipality, People’s Republic of China; 5Prime Physiotherapy Doncaster East, Melbourne, Victoria State, 3109, AustraliaCorrespondence: Xue Deng, Email xdeng1@binghamton.eduAim: Virtual reality (VR) can be analgesic through intercortical modulation. This study investigated neural activities and correlates during different interactive modes.Methods: Fifteen healthy participants (4M, 11F, age 21.93 ± 0.59 years) underwent functional near-infrared spectroscopy (fNIRS) to compare cortical activation and functional connectivity (FC) across brain regions of interest (ROI) and channels (CH) during VR experiences. In the active mode (AM), participants engaged with the virtual environment through motor actions. In the passive mode (PM), participants stood still with their eyes closed, listening to the virtual environment’s music.Results: A better analgesic effect was observed in the AM (t = 3.572, p = 0.001) with higher visual-sensorimotor cortical activation (t = 2.59 to 3.99, p = < 0.001 to 0.015, p-FDR < 0.05). AM showed significant correlations between ratings (pain level and immersion) of VR questionnaire and visual-motor ROIs (r = 0.547 to 0.595, p = 0.013 to 0.038). PM only correlated with pain level and CH 37 (r = 0.608, p = 0.016). FC between S1 and visual-motor-auditory regions was lower in the AM (t = − 4.64 to − 3.53, p = 0.029 to 0.049).Conclusion: VR-induced analgesia occurs via augmenting the visual-sensorimotor-auditory cortical activation, reducing S1 connectivity and weakening pain processing.Keywords: virtual reality, analgesia, functional near-infrared spectroscopy, VR, fNIRS, brain mechanism, functional connectivity, cortical activation